The Runaway Youth - Grinnell, Richard M. (1977)
To date, few (if any) empirically based research studies have been executed in exploring the relationship between the recidivism rate of runaways and the three possible types of dispositions they may receive: (1) counseled and released at the intake level; (2) referred to another social agency; or (3) placed on probation. It is critically pertinent to examine this relationship before attempting to plan alternatives to divert the youths from the juvenile justice system. This article presents the results of an empirically based project where the findings indicate that, regardless of the type of disposition the youths received, they had approximately a 50% chance of returning to the probation department for a subsequent offense